1998
DOI: 10.1523/jneurosci.18-10-03909.1998
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Activity of Hypothalamic Corticotropin-Releasing Hormone Neurons in Transgenic Mice with Impaired Glucocorticoid Receptor Function

Abstract: Loss of central glucocorticoid receptor (GR) function is thought to be involved in the development of neuroendocrine and psychiatric disorders associated with corticotropin-releasing hormone (CRH) hyperactivity. The possible causal relationship between defective GR function and altered activity of CRH neurons was studied in transgenic mice (TG) expressing antisense RNA against GR. Immunocytochemical studies showed significant reductions in CRH immunoreactive neurons in the paraventricular nucleus (PVN) and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 98 publications
1
43
0
Order By: Relevance
“…Chronically elevated levels of central CRH have been shown to cause hyporesponsiveness of hippocampal serotonin following an acute stressful stimulus . In these transgenic mice, hypothalamic release of CRH is low, possibly explaining the enhanced serotonin release (Dijkstra et al 1998).…”
Section: Transgenic Mice Expressing Gr Antisensementioning
confidence: 99%
See 1 more Smart Citation
“…Chronically elevated levels of central CRH have been shown to cause hyporesponsiveness of hippocampal serotonin following an acute stressful stimulus . In these transgenic mice, hypothalamic release of CRH is low, possibly explaining the enhanced serotonin release (Dijkstra et al 1998).…”
Section: Transgenic Mice Expressing Gr Antisensementioning
confidence: 99%
“…This resulted in a mouse expressing GR antisense mainly in neuronal tissue and this mutant was expected to be a well-suited animal model of depression associated with impaired GR function (Pepin et al 1992). This transgenic mouse was extensively studied and the main findings that emerged were the following: 1) these mice needed higher dexamethasone dosages than control mice in order to display corticosterone suppression under basal conditions or following CRH (Stec et al 1994); 2) CRH-elicited ACTH was higher in transgenic mice but corticosterone was lower in comparison to controls ; 3) these mice showed decreased corticosterone response to exogenous ACTH ); 4) when stressed, these mice showed increased ACTH levels, whereas corticosterone levels remain unchanged (Karanth et al 1997); 5) Dijkstra et al (1998) showed reduced activity of CRH neurons in the PVN of these mice and decreased sensitivity of pituitary CRH-R1 mRNA to stimulus-induced desensitisation; 6) these mice displayed an enhanced locomotorstimulating effect to morphine, a response that is reflected by an enhanced dopaminergic activity within the mesolimbic system (Spanagel et al 1996); 7) in these mice, responses to endotoxin were aberrant as noted by Linthorst and coworkers (1999), confirming that immune function is critically determined by appropriate GR function; 8) several studies (e.g., Montkowski et al 1995;Rousse et al 1997;Rochford et al 1997; showed that these mice have impairments in learning and memory paradigms which are also influenced by age; 9) Steckler et al (1999) concluded that allocentric spatial navigation is impaired whereas egocentric navigation is unimpaired. The latter authors suggested that the observed effects were due to hippocampal dysfunction secondary to GR deficiency and possible compensatory changes.…”
Section: Transgenic Mice Expressing Gr Antisensementioning
confidence: 99%
“…Mice with decreased glucocorticoid receptor gene expression (by transgenic expression of antisense mRNA directed against the receptor) exhibit reduced hypothalamic CRH expression [20], enhanced stress-associated ACTH response [21][22][23], and impaired efficiency of glucocorticoid-mediated negative feedback [21,[23][24][25]. These mice exhibit deficits in spatial learning, enhanced responses to novelty and decreased locomotion in familiar environments [6].…”
Section: Modulation By Mineralocorticoid and Glucocorticoid Receptorsmentioning
confidence: 99%
“…Several mouse models with decreased GR activity have been created, including a model whereby a point mutation prevented receptor dimerization (12), a brain-specific GR knockout (13), and a GR-antisense model with reduced expression in brain and some peripheral tissues (14). The latter two models revealed decreased anxiety-like behavior accompanied by profound alterations in the neuroendocrine system (13,(15)(16)(17). Together, these findings led to the hypothesis that a sustained increase in GR activity in brain may be associated with increased anxietylike emotional behavior.…”
mentioning
confidence: 99%